Achievable rates and transceiver design in ultra-wideband communications - Güney, Nazlı. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In a multipath dominated environment, ultra-wideband (UWB) systems that transmit trains of subnanosecond duration pulses exhibit the desirable property of fine resolution in time of the received paths, which as a result of the impulsive form of the transmitted signal go through fewer amplitude fluctuations than those emanating from systems with narrower bandwidths. Being distributed over a large number of resolvable paths, UWB signal energy is typically collected by the rake receiver. In this thesis, achievable information rates of time-hopping M-ary pulse position modulation UWB systems using either soft- or hard-decision outputs are calculated first, where one distinguishing characteristic observed for the hard-output systems is that increasing the constellation size is advantageous only at sufficiently large values of the code rate. Next, it is shown that with time division duplex UWB systems, for which channel information is available at the transmitter, it is possible to move about half of the rake fingers to the transmitter, and simultaneously increase the received signal-to-noise ratio (SNR). The impact of the nature of the noise phenomenon on the rake receiver is such that clipper nonlinearities following the rake fingers are needed if non-Gaussian noise is present. To this end, a robust rake receiver is designed and its performance is optimized through the parameters of the nonlinearities. Finally, a robust multipath-combining decorrelating (mD) detector is developed for non-Gaussian channels. Corresponding to a structure with further processing of the rake receiver outputs, the robust mD detector effectively removes the interference from the other users as well as the impulsive noise, and thus the error floor observed with rake receivers and single-user detection at high SNR values and large number of users is avoided.
Keywords: Ultra-wideband devices.